Genome editing for sickle cell disease: still time to correct? - Ceglie, Giulia; Lecis, Marco; Canciani, Gabriele; Algeri, Mattia; Frati, Giacomo (Frontiers in Pediatrics, 2023)
Sickle cell disease (SCD) is an inherited blood disorder, due to a single point mutation in the β-globin gene (HBB) leading to multisystemic manifestations and it affects millions of people worldwide. The monogenic nature of the disease and the availability of autologous hematopoietic stem cells (HSCs) make this disorder an ideal candidate for gene modification strategies. Notably, significant advances in the field of gene therapy and genome editing that took place in the last decade enabled the possibility to develop several strategies for the treatment of SCD. These curative approaches were firstly based on the correction of disease-causing mutations holding the promise for a specific, effective and safe option for patients. Specifically, gene-editing approaches exploiting the homology directed repair pathway were investigated, but soon their limited efficacy in quiescent HSC has curbed their wider development. On the other hand, a number of studies on globin gene regulation, led to the development of several genome editing strategies based on the reactivation of the fetal γ-globin gene (HBG) by nuclease-mediated targeting of HBG-repressor elements. Although the efficiency of these strategies seems to be confirmed in preclinical and clinical studies, very little is known about the long-term consequences of these modifications. Moreover, the potential genotoxicity of these nuclease-based strategies must be taken into account, especially when associated with high targeting rates. The recent introduction of nuclease-free genome editing technologies brought along the potential for safer strategies for SCD gene correction, which may also harbor significant advantages over HBG-reactivating ones. In this Review, we discuss the recent advances in genome editing strategies for the correction of SCD-causing mutations trying to recapitulate the promising strategies currently available and their relative strengths and weaknesses.